Integrasi Media Sosial Instagram Terhadap UMKM “Mie Ayam Jakarta dan Solo Pak To” Kelurahan Ngagel di Kota Surabaya - Fais, Moh. Ainul; Deviyanti, I Gusti Ayu Sri; Purwoko, Bambang; Rahmanto, Agus; Prihartanti, Wiwik; Widari, Nyoman Sri; Kunhadi, dedy (DHARMA BAKTI, 2024)
MSMEs or commonly called Micro, Small and Medium Enterprises are one of the businesses that have weaknesses in the marketing sector. This task discusses the Marketing of Chicken Noodle MSMEs using Instagram social media. Marketing of this chicken noodle business is only carried out in the area around Ngagel in the city of Surabaya, so the marketing of the chicken noodle business using Instagram social media is expected to be better known by many people and can attract new customers considering the number of Instagram social media users who are quite a lot ranging from small children, teenagers to adults. After carrying out this project task, our hope is that the chicken noodle business can be better known by many people and can attract new customers